The falling elasticity of global trade to economic activity: Testing the demand channel - Marc Auboin; Floriana Borino (World Trade Organization (WTO), 2017)
Since the recovery from the great financial crisis in 2010, global real trade flows grew much slower than pre-crisis, in both absolute terms (growth rates) and relative terms (relative to GDP, from 2:1 in the great 1990's to 1:1 since 2012) A debate has arisen as to whether this global trade slowdown, and related falling trade-to-income elasticity, was structural or cyclical. Some papers emphasized the slowing pace of international vertical specialization. Other works emphasized the prominent role of aggregate demand, notably when weighted by its trade component. Our paper goes in this latter direction. We estimated the standard import equation for 38 advanced and developing countries over the period 1995-2015, using an import intensity-adjusted measure of aggregate demand (IAD), calculated from input-output tables at country level, and compared results with regressions using GDP. The integration of IAD allows us to predict 76% to 86% of the changes in global imports, a better performance than if using GDP. The use of IAD also enabled us to measure the relative importance of each component of demand, according to their trade intensity. The model is able to account for over 90% of the recent trade slowdown (2012-2015), with IAD alone explaining 80% of it. The slowdown in global value chains explains more than half of the remaining share of the global trade slowdown, not explained by demand factors. Protectionism does not come up as statistically significant.
Keywords: E22; F01; F13; F17; F44; 330; investment; global outlook; trade policy; trade forecasting; business cycles